2015
DOI: 10.1039/c4tx00236a
|View full text |Cite
|
Sign up to set email alerts
|

Ah receptor pathway intricacies; signaling through diverse protein partners and DNA-motifs

Abstract: The Ah receptor is a transcription factor that modulates gene expression via interactions with multiple protein partners; these are reviewed, including the novel NC-XRE pathway involving KLF6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 268 publications
(583 reference statements)
0
42
0
Order By: Relevance
“…The AHR is thus an integral component of the mechanism by which DLCs and some PAHs cause toxicity, and loss of AHR function protects against these effects (Fernandez‐Salguero et al., 1996; Goodale et al., 2012; Mimura et al., 1997; Prasch et al., 2003). Although the AHR is now known to participate in a variety of additional, noncanonical interactions and pathways (Jackson, Joshi, & Elferink, 2015), the primary mechanism of toxicity appears to involve canonical interactions requiring nuclear localization, dimerization with ARNT, and binding to AHREs (Bunger et al., 2003, 2008; Nukaya, Walisser, Moran, Kennedy, & Bradfield, 2010; Walisser, Bunger, Glover, Harstad, & Bradfield, 2004). …”
Section: Ahr Pathwaymentioning
confidence: 99%
“…The AHR is thus an integral component of the mechanism by which DLCs and some PAHs cause toxicity, and loss of AHR function protects against these effects (Fernandez‐Salguero et al., 1996; Goodale et al., 2012; Mimura et al., 1997; Prasch et al., 2003). Although the AHR is now known to participate in a variety of additional, noncanonical interactions and pathways (Jackson, Joshi, & Elferink, 2015), the primary mechanism of toxicity appears to involve canonical interactions requiring nuclear localization, dimerization with ARNT, and binding to AHREs (Bunger et al., 2003, 2008; Nukaya, Walisser, Moran, Kennedy, & Bradfield, 2010; Walisser, Bunger, Glover, Harstad, & Bradfield, 2004). …”
Section: Ahr Pathwaymentioning
confidence: 99%
“…AhR-dependent alterations in the expression of genes that lack an apparent AhR DNA (DRE) binding site, coupled with established cross-talk between the AhR and cellular signaling pathways and other transcription factors, suggests that the AhR participates in several novel noncannonical pathways by which the AhR can stimulate gene expression [6,2023]. Ligand-activated AhR can dimerize with nuclear proteins other than ARNT (e.g., Kruppel-like factor 6 (KLF6) and RelB), and these unique heterodimers stimulate gene expression via their interaction with DNA binding sites that are significantly different from that of a DRE [2428] to regulate a unique set of genes (Figure 1). While little is known about the specific protein:protein interactions that occur between the AhR and RelB [24], deletion and functional analysis studies revealed that the mode of AhR:KLF6 dimerization is distinctly different from that of the AhR:ARNT dimer [27].…”
Section: Diversity In Ahr-dependent Mechanisms Of Gene Expressionmentioning
confidence: 99%
“…Its overexpression in transgenic mice suppresses the mCYP1A1 induction in lung, spleen, and adipose tissue [45]. Moreover, it has been suggested that rat CYP1A1 regulates its own expression because it catalyzes the removal of AHR agonists and thus decreases the activation of this pathway [46, 47]. …”
Section: Downregulation Of Cyp1a1mentioning
confidence: 99%